Criteria for designing pedestrian bridges to achieve the aesthetic value in Iraqi cities - Ismael, Zeyad Ali; Mohson, Zainab Hamid; Shalal, Saba Salih (Periodicals of Engineering and Natural Sciences (PEN), 2021)
The Aesthetic Value of pedestrian bridges is measured in the extent of the homogeneity and integration of the bridge with the surrounding Urban scene, which contains and Fulfills functional needs of users. Despite the tremendous technological progress, the design that comes to these bridges is limited to completing the functional aspect as means of crossing between two points. Therefore, this paper studied these bridges and how to achieve the aesthetic value through the theoretical study, in which the aesthetic aspect of these bridges is clarified down to the practical aspect by evaluating the bridges that have been implemented in Iraq and the extent of the success of showing the aesthetic value to the results and recommendations.